2010
DOI: 10.1007/s00484-010-0370-9
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect mortality in Florida during the 2004 hurricane season

Abstract: Previous studies have shown that natural disasters, and hurricanes in particular, have led to more deaths than those usually documented in short post-storm surveys. Such indirect deaths, thought to be related to dietary, stress or pre-existing medical conditions, can exceed the number of direct deaths and may persist for weeks or even months beyond the event itself. In the present study, cumulative sum of deviations plots are used to quantify the number of direct and indirect deaths resulting from Hurricanes C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 34 publications
0
47
0
Order By: Relevance
“…2008). In a somewhat contrasting study during the 2004 hurricane season in Florida, McKinney et al. (2010) found elevated direct and indirect mortality for up to 2 months following each of the four hurricane landfalls in Florida.…”
Section: Societal Impacts and Hazardsmentioning
confidence: 93%
See 2 more Smart Citations
“…2008). In a somewhat contrasting study during the 2004 hurricane season in Florida, McKinney et al. (2010) found elevated direct and indirect mortality for up to 2 months following each of the four hurricane landfalls in Florida.…”
Section: Societal Impacts and Hazardsmentioning
confidence: 93%
“…An average of 60% of the deaths occurred in the post-landfall period and approximately 80% of the deaths were attributed to accidents with trauma being the leading cause of death; followed by drowning, carbon monoxide poisoning, and electrocution (Ragan et al 2008). In a somewhat contrasting study during the 2004 hurricane season in Florida, McKinney et al (2010) found elevated direct and indirect mortality for up to 2 months following each of the four hurricane landfalls in Florida. Direct trauma related deaths accounted for only 4% of storm-related mortality while elevated indirect mortality was linked to heart-related (34%), cancer-related (19%), accident-related (9%), and diabetes-related deaths (5%).…”
Section: Mortality and Morbiditymentioning
confidence: 93%
See 1 more Smart Citation
“…munication, and transportation. 1,29,30,31,32 Identifying vulnerable infrastructure and investing in strategies to reduce vulnerability, including redundancy (having additional or alternate systems in place as backup) and ensuring a certain standard of condition and performance can reduce the likelihood of significant adverse impacts to infrastructure from extreme weather events. 33 Health Risks Related to Infrastructure…”
Section: Disruption Of Essential Infrastructurementioning
confidence: 99%
“…45 In addition, extreme-event-related power outages are associated with increased injuries and deaths from carbon monoxide poisoning after floods, hurricanes, severe winter storms, and ice storms. 1,31,46,47,48,49 This is due to increased use of gasoline-powered generators, charcoal grills, and kerosene and propane heaters or stoves inside the home or other areas without proper ventilation (see also Ch. 3: Air Quality Impacts).…”
Section: Disruption Of Essential Infrastructurementioning
confidence: 99%